2019
DOI: 10.1016/j.conctc.2019.100318
|View full text |Cite
|
Sign up to set email alerts
|

Digital recruitment and enrollment in a remote nationwide trial of screening for undiagnosed atrial fibrillation: Lessons from the randomized, controlled mSToPS trial

Abstract: ObjectivesThe advent of large databases, wearable technology, and novel communications methods has the potential to expand the pool of candidate research participants and offer them the flexibility and convenience of participating in remote research. However, reports of their effectiveness are sparse. We assessed the use of various forms of outreach within a nationwide randomized clinical trial being conducted entirely by remote means.MethodsCandidate participants at possibly higher risk for atrial fibrillatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 12 publications
2
26
2
Order By: Relevance
“…24 Outreach in Early Check was several times more effective than recruitment outcomes observed in other large-scale studies using direct-mail and email outreach, where reported enrollment rates from these methods range from less than 1% to 2% [25][26][27] . Although Baca-Motes et al 28 achieved a 9% enrollment rate from an optimized recruitment campaign comprising three emails plus two mailings sent over a 3-week period, their enrollment rates from direct mail alone, email alone, or an email with a single reminder did not exceed 1%. Our findings indicate that the reminder postcards were ineffectual, and we…”
Section: Accepted Articlementioning
confidence: 93%
“…24 Outreach in Early Check was several times more effective than recruitment outcomes observed in other large-scale studies using direct-mail and email outreach, where reported enrollment rates from these methods range from less than 1% to 2% [25][26][27] . Although Baca-Motes et al 28 achieved a 9% enrollment rate from an optimized recruitment campaign comprising three emails plus two mailings sent over a 3-week period, their enrollment rates from direct mail alone, email alone, or an email with a single reminder did not exceed 1%. Our findings indicate that the reminder postcards were ineffectual, and we…”
Section: Accepted Articlementioning
confidence: 93%
“…The Brain Health Registry (BHR) ( brainhealthregistry.org ) collects longitudinal health, cognitive, and lifestyle data through detailed self-report questionnaires and online cognitive tests (Cogstate, Lumosity, and MemTrax) ( 16 ). BHR was launched in 2014 and currently has baseline data on 56,982 participants.…”
Section: Methodsmentioning
confidence: 99%
“…Going further than remote recruitment, Orri et al ( 14 ) conducted the first entirely web-based clinical trial run under an Investigational New Drug (IND) application. Digital tools allow researchers to optimize the use of mobile technologies in clinical trials, respond to the preferences of participants ( 15 ), and measure and finetune communication methods ( 16 ). To our knowledge, TRC-PAD is the first program inviting participants from various existing registries to a join a longitudinal Webstudy with identification and referral of high-risk individuals to an in-person TRC.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a large-scale remote clinical trial (mSToPs study) using a wearable ECG patch were recently introduced. In this study, major processes such as participant recruitment, informed consent, the delivery of wearable devices, data collection, and observation of clinical courses were performed remotely using a smartphone and electronic medical records [ 52 ]. Results showed that, the diagnostic rate of atrial fibrillation was significantly higher in users who used the ECG patch early [ 53 ].…”
Section: Remote Clinical Trialmentioning
confidence: 99%